ANALISIS YURIDIS TERHADAP DISPARITAS PUTUSAN HAKIM YANG PELAKUNYA MENGALAMI SKIZOFRENIA (Studi Putusаn Nomor: 94-K/PM.II09/АD/V/2016 dan Putusаn Nomor: 109-K/PM.III 12/АL/VI/2017) - I Komang Sanju Bayu Mustika; Made Sugi Hartono; Ni Ketut Sari Adnyani (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to analyze and examine the disparity in the decisions of judges whose perpetrators have schizophrenia. In order to answer the formulation of the problem in this study, the normative legal research method was used, namely research conducted by examining two similar judge's decisions. In this study, it examines the disparities of two similar judges' decisions whose perpetrators have schizophrenia. Through this research method, the results are obtained that criminal responsibility for people with mental disorders is regulated in article 44 of the Criminal Code. However, even though it has been regulated in Article 44 of the Criminal Code, judges in deciding cases have the authority regulated in law to decide cases according to their wishes. Indirectly this authority can lead to different interpretations between judges in deciding a case so that disparities arise in decisions of the same kind. As an example in Decision Number: 94-K/PM.II09/AD/V/2016 and Decision Number: 109-K/PM.III-12/AL/VI/2017. The two decisions have several similarities, namely, the two perpetrators are both active members of the TNI and suffer from schizophrenia. However, there was a disparity in the judge's decision in the two cases, namely in the first decision the judge imposed a prison sentence on the defendant, while in the second decision the judge decided to acquit the defendant from all charges. Therefore, in deciding a case, the judge must be observant in assessing the psychological condition of a defendant in which the judge must be assisted by an expert in handling cases as described above so that this can provide legal certainty from Article 44 of the Criminal Code itself.